2019
DOI: 10.22161/ijaers.611.32
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Mechanical Properties of Concrete with Addition of Bamboo Fiber - Porto Nacional/TO

Abstract: The search for materials which do not unduly the environment by reducing the cost of production is increasing throughout the world. In the construction sector, concrete is the most consumed material in the world. Its production with bamboo fiber addition can contribute to minimize environmental impacts and production costs by reducing the extraction of natural resources. This study aimed to investigate the mechanical properties of bamboo located in the region of Porto Nacional -TO, Brazil and its application a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
3
0
1
Order By: Relevance
“…The quantity of water used in the concretes with admixtures included the liquid portion of the admixture without considering the solid portion. All the concretes were produced in a stationary concrete mixer using the same procedures [9], sequence, and mixing time. Table 3 shows the densities of the produced concretes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The quantity of water used in the concretes with admixtures included the liquid portion of the admixture without considering the solid portion. All the concretes were produced in a stationary concrete mixer using the same procedures [9], sequence, and mixing time. Table 3 shows the densities of the produced concretes.…”
Section: Methodsmentioning
confidence: 99%
“…Lightweight concrete is widely used in the construction industry [5] and is categorized as lightweight aggregates, aerated, and foamed concrete. Lightweight concrete can be produced by adding lighter materials to the mixture to replace conventional materials such as glass foams [6,8], bamboo fibers [9], waste PET bottles [10], glass bottles [11], or the addition of air-entraining admixtures (AEAs), which are used in order to create macro pores that reduce the pressure of ice formation in the binding matrix. Air-entraining additives were discovered in the 1930s in New York City after concrete collapsed, and air-entraining agents are primarily used to ensure a quality air void system that protects concrete from frost damage.…”
Section: Introductionmentioning
confidence: 99%
“…The global trend towards building taller structures has escalated concrete production, making it the most utilized material worldwide [11][12][13][14], with annual production nearing 10 billion cubic meters [15]. Research has indicated that construction processes can integrate various waste materials into concrete, such as vitreous foams [7,8], bamboo fibers [16], PET bottles [17], and glass bottles [18], to mitigate environmental impacts.…”
Section: Introductionmentioning
confidence: 99%
“…Quando comparado o concreto convencional com o concreto reforçado com fibra de bambu, a resistência à compressão do concreto reforçado com fibra de bambu a 0,5%, 1%, 1,5%, e 2% aumentou, mas reduziu para 2,5% em comparação com outras proporções de fibras. Ferreira et al (2019) investigou os resultados da resistência à compressão uniaxial aos 28 dias dos corpos-de-prova produzidos com a substituição parcial da areia pela fibra de bambu. As fibras de bambu e agregados foram caracterizados e avaliados de acordo com o material e definido pelo traço (1: 1,68: 2,68: 0,482), com percentuais de substituição parcial da areia pela fibra de bambu nas concentrações de 3%, 4% e 5%.…”
Section: Introductionunclassified